Application of zero waste farming system technology for the empowerment of farmers and breeders in Sigi Regency, Central Sulawesi - Hasriyanty Hasriyanty; Burhanuddin Haji Nasir; Sulaeman Sulaeman; Sri Anjar Lasmini (Community Empowerment, 2024)
The Covid-19 pandemic affects all sectors, including agriculture. Challenges faced by the "Belo Singgani" Livestock Farmer Group include a lack of skills in enhancing agricultural productivity at a macro level, resulting in low marketability of agricultural products, and insufficient community engagement and awareness regarding agricultural maintenance and utilization. To address these issues, implementing zero waste farming system technology, specifically integrated farming techniques, is proposed as a solution. The Community-based Empowerment Program (PBM) aims to support the community in implementing a zero waste farming system for economic empowerment post-Covid-19. Methods employed include training, demonstration plots, and community assistance. Results from the community service initiative indicate an 80% increase in participants' knowledge about zero-waste farming systems and 60% of participants successfully utilizing waste to produce organic fertilizer. This is evidenced by the production and utilization of organic fertilizer, contributing to the development of a sustainable zero waste farming system.